Looking for an unexpected heidegger’s philosophical anthropology - Braga, José Olinda (Revista de Psicologia, 2016)
There is a possibility of seizing an unexpected Philosophical Anthropology resulting from Existential Analytic of Dasein undertaken by Martin Heidegger in Being and Time - although this was not his philosophical intention. His positions assumed in Zöllikon conference through dialogue with his fundamental ontology, is unequivocally an essential foundation for reflection and development of the human sciences in general and psychology and psychopathology phenomenological in particular. This task must to be performed through scientific and philosophical researches, in parallel, as a essential mission needed to base the practice of human sciences that claim for epistemological foundations in order to provide them to the advent of new scientific productions, and needed elements for inspired thoughts founded in existential-phenomenological precepts, according to their conceptions of intersubjectivities and otherness cooriginatedly expressed in lived stories, times and spaces. The dialogue between science and philosophy, largely imposes the need for a precise distinction between what is assumed as object for those two different sources of production of knowledge, remain in the instance of a mutual incitement, as a condition of possibility for the development and justification of both.